Analyzing the Expression Level and Cellular Location of the Tip-1 Protein in Oral Cancer Cell Lines - N Mansoursamaei (Tehran University of Medical Sciences, 2005)
Oral squamous cell carcinoma (OSCC) is the sixth most common cancer in the world and accounts for approximately 4% of all cancers and 2% of all cancer death.The single most important factor in the prevention of the disease is early detection although, due to increased risk of secondary malignancy, survival remains poor with only a 25% 5 years survival. Both hereditary and environmental factors have been shown to have a productive role in this disease. For example, although chronic exposure of oral epithelium to tobacco smoke and alcohol are amongst the most important aetiological factors, it is now becoming realized that infection with high risk types of human papilloma virus (HPV) are also involved as causative agent in a subset of this disease. All of these OSCC associated factors are known to promote genetic instability in the target oral epithelial cells. Work in our laboratories has indicated that the Tax interacting protein 1 (Tip-1) is also a target for the HPV 16 E6 protein may play an important role in controlling genetic instability during the oncogenic process (Hampson L., et al unpublished). So far 14 oral cancer cell lines have been grown in cell culture and RNA extracted from these. Tip-1 transcript levels were analyzed in this material by Northern blotting and competitive template quantitative PCR, which showed that Tip-1 levels were higher in some, cell lines than others (4 high, 6 moderate, 4 low level). Cell ploidy was determined by FACS analysis of propidium iodide stained cells, which showed that out of all the OSCC cell lines tested the cell line (BICR 68) had the greatest numbers of polyploid cells and also had the highest expression of Tip-1 RNA.